SOCIAL MOVEMENT RESISTANCE AGAINST THE STATE SOCIAL CASE STUDY: PTPN DAMAK MALIHO, BANGUN PURBA DISTRICT, 2008-2009. - Ansyari Harahap, Andry; malik, Rahman (Journal of Peasants' Rights, 2022)
The study is about the Resistance movement against the state social case study PTPN Damak Maliho in ancient 2008-2009. The main discussion is between peasants’ groups with PTPN IV at deli Serdang district, Damak Maliho, and the role of peasants’ groups in reversion land rights. The conclusion is that the root of the problem is a scramble for the land of 198 ha state of the community with PTPN IV in Damak Maliho, Bangun Purba's District, Deli Serdang is a state of each other claims of land between the village community with PTPN IV of 198 acres of land. Second, the strategy is taken by leaders the base states peasants’ village Damak Maliho to demand land rights by occupying the land. Third, analysis Karl Marx saw the result of this research concluded that countries' indecisiveness in seeing the conflicts causes losses to peasants.